Themes and styles in some selected Qasidas: a new historicist study - Abike, Mustapaha Madinat (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
The pre Islamic Arabic ode, Qasida is a verse form that persisted as the prevailing Arab-Islamic poetic form from 500 A.D. to the first half of our century. It had great impact on the Arabic language, literature, rhetoric, folk traditions and poetry. This tradition has spread all over the world and has inspired poets to write panegyrics in their native languages. It has been written in Persian, Urdu, and African languages. The Muallaqat are recognized to be extraordinary during the pre-Islamic period because they are the winners of annual poetry competitions and are suspended on the walls for everyone to read; they therefore act as, and are recognized as the original form of the Qasida. The verse form is predominately used in literary works before now following a traditional structure, with themes and motifs related to the happenings of the social, political and economic settings of the pre-Islamic era. These poetic forms survived evolution throughout the literary world. Although some forms have emerged through literary innovations, some still imitated the earlier structure of classical Qasida. For instance, the Qasida Burdah was produced 650 years after the demise of the Prophet (saw) but still retains some of the fundamental elements from the earlier structure. This research therefore examines the changes in the themes and styles of the Qasida during its historical evolution between the sixth and the twentieth century using the new historical theory. It also describes the exact nature of the Qasida in the past six centuries to show the pattern of development in their themes and styles. The findings showed changes and varieties in the themes and styles that have emerged from the classical period to this contemporary period.